IITA DG Sanginga inaugurates renovated facilities of Virology and Germplasm Health Units - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
The renovation expands our capabilities to use new technologies and improve the learning environment for staff and students working on a range of topics in virology, diagnostics, phytosanitation, seed health testing, epidemiology, phenotyping, and others.